KAFIRNYA FILSUF MUSLIM: Ibn Rusyd Meluruskan al-Ghazali - Muhammad Mahfud Ridwan (IAIN Tulungagung, 2016)
Ibn Rusyd is seen figure renewal and generating Aristotle philosophy that has long been buried or torpor. Among his famous works is about criticism of al-Ghazali thought about keqadiman nature, knowledge of God and theresurrection of man. Ibn Rusyd argued about the views of the philosophersof the latter. Al-Ghazali accusations against the philosophers is not truebut just different points of view are made as if the philosophers have deviated from monotheism even considered infidels.Keywords: Ibn Rusyd, al-Ghazali, critics